Thyrotoxicosis, Etiology, Presentation and Management Challenges in Nigeria: A Review of Cases Seen Over a 5 Year Period - Onyenekwe, Belonwu Mends (European Scientific Journal, ESJ, 2019)
Background: Thyrotoxicosis is a common endocrine disorder worldwide with a female predominance. Graves disease is reported as the commonest cause of thyrotoxicosis by various authors in the Africa region. Aims and Objectives: The study evaluated patient characteristics, clinical and laboratory profile, co-morbidities, treatment modalities, response to therapy, side effects of anti-thyroid medications, treatment outcome and complications of the disease in patients with thyrotoxicosis. Materials and methods: This study was retrospective and observational. The records of patients diagnosed with overt thyrotoxicosis seen in the Endocrine unit (2013-2017) were pulled and relevant data compiled. Data was analyzed using SPSS V 21. Results: A total of 172 cases were studied; 33 males and 132 females (ratio 1:4). They were aged 18-70; 40.2 Â±12.5 years. Graves Disease constituted 79 % 0f cases and toxic multinodular goiter made up 18%. Seven cases of Marine Lenhart syndrome were identified. Graves orbitopathy occurred in 54%, but was mild. All but 6 patients received anti-thyroid medication as initial therapy mainly carbimazole (90%). About 6% had thyroidectomy. Treatment default was high (52%), while 15% remitted and 19% relapsed. Total duration of illness was 1- 380, 40.7 Â± 52.6 months. Drug rash occurred in 5% and cholestatic hepatitis in 1.8%. Hypertension coexisted in 35%. Six pregnancies were recorded, four of which ended in miscarriages, two of which had thyroid storm. Heart disease complicated the disease in 36%. Conclusion: Thyrotoxicosis is a common clinical condition. Treatment with carbimazole is effective. However the treatment default rate was very high. Coexisting hypertension and pronlonged period of untreated disease exposed patients to a high burden of heart disease. Patient education and introduction of radioablation therapy will mitigate these challenges.